Novel Magnetic Cross-Linked Cellulase Aggregates with a Potential Application in Lignocellulosic Biomass Bioconversion - Junqi Jia; Weiwei Zhang; Zengjie Yang; Xianling Yang; Na Wang; Xiaoqi Yu (Molecules, 2017)
The utilization of renewable biomass resources to produce high-value chemicals by enzymatic processes is beneficial for alternative energy production, due to the accelerating depletion of fossil fuels. As immobilization techniques can improve enzyme stability and reusability, a novel magnetic cross-linked cellulase aggregate has been developed and applied for biomass bioconversion. The crosslinked aggregates could purify and immobilize enzymes in a single operation, and could then be combined with magnetic nanoparticles (MNPs), which provides easy separation of the materials. The immobilized cellulase showed a better activity at a wider temperature range and pH values than that of the free cellulase. After six cycles of consecutive reuse, the immobilized cellulase performed successful magnetic separation and retained 74% of its initial activity when carboxylmethyl cellulose (CMC) was used as the model substrate. Furthermore, the structure and morphology of the immobilized cellulase were studied by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Moreover, the immobilized cellulase was shown to hydrolyze bamboo biomass with a yield of 21%, and was re-used in biomass conversion up to four cycles with 38% activity retention, which indicated that the immobilized enzyme has good potential for biomass applications.